Peran Stakeholder dalam Komodifikasi Tradisi Perkawinan Hindu pada Paket Wisata Weeding di Kawasan Wisata - I Ketut Arta Widana (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2017)
The development of cultural tourism has made any cultural products, profane and sacred, become comodity. The process of commotitisation is due to the need of many stakeholders in achieving the goal. The stakeholders playing important roles in the process of commoditisation according to the concept of “key actors” in tourism are government, local people, the tourists,media, industry, and the non-government organization. The commoditisation of traditional Hindu wedding in Ubud Tourism Resort (kawasan Wisata Ubud) is enabled by the meet of tourists motivation as the consummers and the other stakeholders as the supplier. The irrational motivation of the tourists to experience the autenticity with high buying power has made the tourism system in the hosts’ side fulfil the tourists expectation for the sake of material achievement. Government has made restriction in conducting the traditional wedding to the tourists that made the wedding organizer respect the local tradition and socialize the restriction through thepromotion website they have. But commoditisation can not be avoided since the locals don’t mind to serve their tradition as a tourist product to purchase in the secular industry.